Studi Literatur: Konsep Dan Upaya Kuratif Kecanduan Game - Siti Aisyah; Wiryo Nuryono; Ari Khusumadewi; Bakhrudin All Habsy (Universitas Nusantara PGRI Kediri, 2025)
Online gaming addiction has emerged as a critical behavioral disorder affecting adolescents' psychological health and academic performance. This study aims to describe the core concepts, impacts, and effective curative strategies to address this digital phenomenon. The methodology employs a systematic literature review by synthesizing diverse scientific references and empirical data (Saputra, 2017). Results indicate that multidisciplinary interventions involving the synergy of families, educational institutions, and government policies are the most optimal approach. The discussion highlights that Cognitive Behavioral Therapy (CBT), Solution-Focused Brief Therapy (SFBT), and self-management techniques are highly relevant for enhancing self-regulation and personal responsibility. These integrated approaches provide a robust framework for counselors to mitigate the long-term consequences of gaming addiction effectively.